Cardioprotective and Hepatoprotective Effects of Ixora pavetta and Tecoma capensis Leaf Extracts - Suneeta, Dara; Rao, YRKV Tirupathi (International Journal of Pharmaceutical Investigation)
Background: Ixora pavetta and Tecoma capensis are two less explored and neglected plants species in medicinal prospective. The flowers bark and root of I. pavetta used as a remedy for cough, anaemia, women urinary problems. The bark powder of Tecoma capensis useful in treating fever, pneumonia, stomach problems and improve blood clotting. The role of leaves from these plants in medical practices is not yet clearly determined. The present work aimed to examine the potentiality of their leaf extracts in treating cardiovascular and chronic liver diseases. Materials and Methods: Solvent extraction method is used to extract the bioactive components. The leaf extracts were tested for the existence of cardiac glycosides. The cardioprotective activity and hepatoprotective activity were done using isoproterenol method and MTT assay respectively. Results: The leaf extracts of both plants showed the presence of cardiac glycosides and the leaf extracts of T. capensis recorded a high yield of cardiac glycosides. Leaf methanolic extract (200 mg/kg) of T. capensis exhibited significant depletion in total cholesterol 108.11 mg/dL, tryglcerides 81.48 mg/dL and LDL cholesterol 93.15 mg/ dL in Wistar rats. The I. pavetta leaf methanolic extracts recorded moderate protective activity by increasing the concentrations against H2O2 pre-stimulated HepG2 cells. Conclusion: The extracts of both plants exhibited good cardioprotective activity and hepatoprotective activity. The leaf methanolic extracts of T. capensis reported more cardioprotective activity whereas the leaf methanolic extracts of I. pavetta showed significant hepatoprotective potentiality.
Keywords: Cardiac glycosides; Bioactive compounds; Cholesterol; Triglycerides; HepG2 cells.